2014
DOI: 10.1016/j.mbs.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A generalized free-solvent model for the osmotic pressure of multi-component solutions containing protein–protein interactions

Abstract: a b s t r a c tThe free-solvent model has been shown to have excellent predictability of the osmotic pressure for single and binary non-interactive proteins in aqueous solutions. Here the free-solvent model is extended to be more generalized by including the contributions of intra-and inter-protein interactions to the osmotic pressure of a solution in the form of homo-and hetero-multimers. The solute-solvent interactions are considered to be unique for each homo-and hetero-multimer in solution. The effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…However, because of the nearly unobserved ion binding, the osmotic pressures of NaI and NaSCN were over 50 kPa higher than that of NaF. We showed previously that at high self-crowded concentrations, the FSB model predicts that increase in ion binding can deaccelerate the increase in osmotic pressure with respect to increasing concentration …”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…However, because of the nearly unobserved ion binding, the osmotic pressures of NaI and NaSCN were over 50 kPa higher than that of NaF. We showed previously that at high self-crowded concentrations, the FSB model predicts that increase in ion binding can deaccelerate the increase in osmotic pressure with respect to increasing concentration …”
Section: Resultsmentioning
confidence: 92%
“…[46][47][48][49][50][51] However, we have shown that, via our FSB model, the bulk property, osmotic pressure, of self-crowded proteins and crowded binary globular protein solutions can directly provide ion binding and hydration properties of proteins, specifically in the highly crowded regions where the rate of change of osmotic pressure to protein concentration is highly non-linear. [52][53][54][55][56][57][58][59][60][61][62][63] Because the FSB model focuses on protein hydration and ion-binding, it can provide a fortuitous approach in interrogating anion effects on crowded protein solutions.…”
Section: Relevance Of Osmotic Pressure In the Interpretation Of Anionmentioning
confidence: 99%
See 3 more Smart Citations